Recycling of perfluorosulfonic acid-based membranes and their Re-application in PEM fuel cells - Kutter, Maximilian; Greve, Christopher; Maier, Maximilian; Schilling, Monja; Mauel, Anika; Hilgert, Annika; Hoffmann, Hendrik; Hagemeier, Wiebke; Rosin, Andreas; Muggli, Mark; Zeis, Roswitha; Senker, Jürgen; et al. (Journal of Membrane Science, 2024)
Polymer electrolyte membrane fuel cells (PEMFC) are lagging in commercialization due to the high cost of noble metal catalysts (e.g., Pt) and perfluorosulfonic acid-based (PFSA) membranes. Recycling and reusing these components at the end of life (EoL) could increase the viability and decrease the environmental impact of PEMFCs. In this work, we demonstrate an environmentally friendly method for reprocessing PFSA membranes based on a hydrothermal treatment using only water as a reactant, which is essential for upscaling to an industrial application. In addition, we focused on the recycling process itself and the membrane's recovery as a water-based dispersion, but also investigated the structural, chemical, and mechanical properties and the electrochemical performance of the membranes after being re-cast from the water-based dispersion (denoted as reprocessed membranes). We investigated two different ionomers, a short-side chain (SSC) ionomer with an equivalent weight of 800 (3M-800EW) and a long-side chain (LSC) ionomer with an equivalent weight of 1000 (3M-1000EW), both obtained from 3 M. Both membrane types could be dispersed in water and reprocessed by hydrothermal treatment. No changes in the chemical structure of the ionomers were observed by subsequent IR, Raman, and NMR spectroscopy. However, thermal and mechanical analyses of the reprocessed membranes showed a deterioration of their mechanical properties. The hydrothermal step increased both the water uptake and retention behavior. We attribute this to the expansion of the water channels observed in the SAXS analysis. Full cell tests under standard (80 °C) and harsher (120 °C & 130 °C) operation conditions demonstrated electrochemical performance for the reprocessed 800EW membranes.
CRIS-Team Scopus Importer:2024-01-05
Keywords: In-situ Raman; PEM fuel cells; PFSA recycling; PFSA reprocessing; SAXS study; Solid-state NMR spectroscopy; Water retention